Effect of varying levels of nitrogen and plant density on the production behaviour of undersize seed tubers of potato (Solanum tuberosum) in north-western hills of India - SHARMA, ASHWANI KUMAR; KUMAR, VINOD (The Indian Journal of Agricultural Sciences, 2014)
Production potentiality of undersize (15g) seed tubers of potato (Solanum tuberosum L.) variety Kufri Giriraj was evaluated at three plant densities, viz. 83 333; 111 111 and 166 666 plants /ha and four doses of nitrogen in high hills of north –western India. Both, plant density as well as nitrogen doses had a significant effect on the number as well as yields of total and seed size tubers. A plant density of 166 666 plants/ha with 160 kg nitrogen/ha resulted in maximum number of total and seed size tubers as well as yields. Thus, in the hills, under size (15 g) seed tubers of potato should be planted at a plant density of 166 666 plants/ ha by following 60 cm × 10 cm spacing along with a nitrogen dose of 160 kg/ha for getting the maximum number as well as yields of total and seed size (20-80g) tubers.